2019
DOI: 10.1177/1032373219870316
|View full text |Cite
|
Sign up to set email alerts
|

The formation and use of a profit reserve at the end of the fourteenth century

Abstract: This article analyses the earliest known use of reserve accounting in the late fourteenth century. It reveals the dual purpose of this reserve, the entries made, including those made when the reserve was utilized and when the remainder was written-back to be distributed to the owners in the following accounting period. The research method is archival, using logical–analytical modelling of a merchant’s accounting records from 1392 to 1400. It finds that a reserve was initially an estimate of costs that had been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…8. Among the most recent studies in the history of accounting that have used documentation from Datini's companies, we mention Kuter et al (2017Kuter et al ( , 2018Kuter et al ( , 2020. 9.…”
Section: Discussionmentioning
confidence: 99%
“…8. Among the most recent studies in the history of accounting that have used documentation from Datini's companies, we mention Kuter et al (2017Kuter et al ( , 2018Kuter et al ( , 2020. 9.…”
Section: Discussionmentioning
confidence: 99%
“…Many articles contained biographical details of a person involved in the professionalisation of accounting including their death (e.g. Bisman, 2012; Carnegie, 2005) or some figure that has presided over the keeping of accounts, such as Tsar of Russia Peter I (see Sokolov, 2019) or the international trader Francesco di Marco Datini (see Kuter et al, 2020). In these articles there were no accounts for or account of death.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, the Datini archives show a transition from single entry bookkeeping to double entry bookkeeping around 1383. Kuter, et al (2019) found that the account books of partnerships were closed, and the profit distributed among the partners at various points prior to the final dissolution of the companies. However, there is no evidence that the accounting records of the Datini companies were closed and profits determined on regular basis, such as annually.…”
Section: The Use Of Time In the Datini Enterprises In Northern Italy mentioning
confidence: 99%